Lnc90386 Sponges miR-33-5p to Mediate Mycoplasma gallisepticum-Induced Inflammation and Apoptosis in Chickens via the JNK Pathway - Sun, Yingfei; Wang, Yingjie; Zou, Mengyun; Wang, Tengfei; Wang, Lulu; Peng, Xiuli (Frontiers in Immunology, 2022)
Mycoplasma gallisepticum (MG) is one of the most important pathogens, that causes chronic respiratory disease (CRD) in chickens. Long non-coding RNAs (lncRNAs) are emerging as new regulators for many diseases and some lncRNAs can function as competing endogenous RNAs (ceRNAs) to regulate mRNAs by competitively binding to miRNAs. Here, we found that miR-33-5p was significantly up-regulated both in MG-infected chicken embryonic lungs and chicken embryo fibroblast cells (DF-1), and Lnc90386 negatively correlated with miR-33-5p. miR-33-5p, as a new regulator for MG infection, repressed apoptosis, inflammatory factors in DF-1 cells by targeting JNK1. Further analyses showed that Lnc90386 sponged miR-33-5p to weaken its inhibitory effect on JNK1, forming the ceRNA regulatory network. Furthermore, knockdown of Lnc90386 significantly inhibited apoptosis and inflammatory factors, and promoted DF-1 cells proliferation. However, co-treatment with miR-33-5p inhibitor and Lnc90386 siRNA showed that knockdown of Lnc90386 could partially eliminate the inhibiting effect of miR-33-5p inhibitor on inflammation, cell apoptosis and proliferation. In conclusion, Lnc90386 sponges miR-33-5p to defend against MG infection by inhibiting the JNK signaling pathway.